Search for indicators that determine the effectiveness of overcoming acyclic sections at 50, 100 and 200 meters in freestyle swimming - Politko, E.; Teslenko, I. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to establish the most significant indicators affecting the athletic performance of highly skilled swimmers during the overcoming of acyclic sections at 50, 100 and 200 meters in freestyle swimming.